Zagadnienia prawa zwyczajowego w badaniach Andrija Jakowliwa - Bedrìj, Mar'ân (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
Andriy Yakovliv 1872–1955 was a well-known law and history researcher, social activist and politician, one of the founders of Ukrainian legal science in the Diaspora, and a prominent representative of Ukrainian legal thought in the 20th century. During the Ukrainian Revolution of 1917–1921 he showed his political and administrative skills in important positions in the power system of the Ukrainian state. After its fall, he led a political and scholarly activity in exile in Czechoslovakia and the Republic of Poland, and after World War II in Belgium and the United States. Among Yakovliv’s scientific considerations on the subject of law, special attention is deserved by the problems of customary law. These researches are reflected in his numerous works.Customary law issues in Yakovliv’s research can be divided into three main blocks: the concept and nature of customary law; form of legal customs; organization and activity of customary law courts. He systematized the existing approaches to understanding the customary law into three groups: mechanical decisive in the context of the legal nature of the custom is a fact of uniform and long-standing observance of a certain type of behavior; spiritualistic they recognize the primacy of legal custom internal standing;mixed concurrently importance of both factors – implementation and recognition of legal customs.
Keywords: Jakowliw, Andrij; prawo zwyczajowe; prawo ukraińskie; przysłowia ludowe; sądy kopne